Area-specific analysis of the distribution of hypothalamic neurons projecting to the rat ventral tegmental area, with special reference to the GABAergic and glutamatergic efferents - Imre eKalló; Imre eKalló; Csilla S. Molnár; Sarolta E. Szőke; Erik eHrabovszky; Csaba Liposits Fekete; Csaba Liposits Fekete; Zsolt eLiposits; Zsolt eLiposits (Frontiers Media S.A., 2015)
The ventral tegmental area (VTA) is a main regulator of reward and integrates a wide scale of hormonal and neuronal information. Feeding-, energy expenditure-, stress, adaptation- and reproduction-related hypothalamic signals are processed in the VTA and influence the reward processes. However, the neuroanatomical origin and chemical phenotype of neurons mediating these signals to the VTA have not been fully characterized. In this study we have systematically mapped hypothalamic neurons that project to the VTA using the retrograde tracer CTB and analyzed their putative GABA and/or glutamate character with in situ hybridization in male rats. 23.93±3.91% of hypothalamic neurons projecting to the VTA was found in preoptic and 76.27±4.88% in anterior, tuberal and mammillary hypothalamic regions. Nearly half of the retrogradely-labeled neurons in the preoptic, and more than one third in the anterior, tuberal and mammillary hypothalamus appeared in medially located regions. The analyses of VGLUT2 and GAD65 mRNA expression revealed both amino acid markers in different subsets of retrogradely-labeled hypothalamic neurons, typically with the predominance of the glutamatergic marker VGLUT2. About one tenth of CTB-IR neurons were GAD65-positive even in hypothalamic nuclei expressing primarily VGLUT2. Some regions were populated mostly by GAD65 mRNA-containing retrogradely-labeled neurons. These included the perifornical part